Effects of 3 Weeks of Water Immersion and Restraint Stress on Sleep in Mice - Yasugaki, Shinnosuke; Liu, Chih-Yao; Kashiwagi, Mitsuaki; Kanuka, Mika; Honda, Takato; Miyata, Shingo; Yanagisawa, Masashi; Hayashi, Yu (Frontiers in Neuroscience, 2019)
Repeated stress is a risk factor for mental disorders and can also lead to sleep disturbances. Although the effects of stress on sleep architecture have been investigated in rodents, the length of the stress exposure period in most studies has been limited to about 10 days, and few studies have analyzed the effects of chronic stress over a longer period. Here we investigated how sleep is affected in a mouse model of depression induced by 3 weeks of daily water immersion and restraint stress (WIRS). Sleep was recorded after 1, 2, and 3 weeks of stress exposure. Some stress-induced changes in several sleep measures were maintained across the 3 weeks, whereas other changes were most prominent during the 1st week. The total amount of non-rapid eye movement sleep (NREMS) was increased and the total amount of time spent awake was decreased across all 3 weeks. On the other hand, the amount of REMS during the dark phase was significantly increased in the 1st week compared with that at baseline or the 2nd and 3rd weeks. Electroencephalogram (EEG) power in the delta range was decreased during NREMS, although the total amount of NREMS was increased. These findings indicate that repeated WIRS, which eventually leads to a depression-like phenotype, differentially affects sleep between the early and subsequent periods. The increase in the amount of REMS during the dark phase in the 1st week significantly correlated with changes in body weight. Our results show how sleep changes throughout a long period of chronic stress in a mouse model of depression.